Antisipasi Kegawatdaruratan Post Partum Melalui Pengenalan Tanda Bahaya Post Partum di RSIM Sumberejo Bojonegoro - Ponco Indah Arista Sari; A.R Tyas Avianthi; Yevi Octa Mahardika (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2022)
Complications or emergencies during the puerperium are usually rare during pregnancy patients receive quality care, starting from pregnancy until delivery. If the patient frequently face to face with the midwife through antenatal checks then midwives have more opportunities to do screening for various possible complications may appear during inpartu and puerperium. Complications during the puerperium sometimes cannot be known in advance, but can also occur suddenly. From this it is felt that it is very important to introduce mothers to the danger signs of the postpartum period. In RSIM there are mothers giving birth to approximately 20 people every month. but not all mothers have received the information needed during the puerperium. This community service activity is carried out by providing health education to postpartum mothers. To find out the success of the activity, a pretest on the danger signs was carried out then a post test was carried out for the danger signs. From the results of community service, there were 87% of mothers who had good knowledge after being given health education. they understand about the danger signs of the postpartum period and its detection. From this, it can be concluded that the importance of communication, information and education should be given to mothers starting from pregnancy about the danger signs of parturition and early detection.